Electrophysiological mechanisms of biased response to smoking-related cues in young smokers. (26th August 2016) - Cheng, Jiadong; Guan, Yanyan; Zhang, Yajuan; Bi, Yanzhi; Bu, Limei; Li, Yangding; Shi, Sha; Liu, Peng; Lu, Xiaoqi; Yu, Dahua; Yuan, Kai
Highlights: Brain responses were compared between young smokers and controls by employing ERP. Abnormal cognitive processing of smoking-related cues was observed in young smokers. The SPW of smoking-related cues was enhanced in young smokers compared with controls. P300/SPW of smoking-related cues was larger than neutral cues in young smokers. A positive correlation between CPD and P300/SPW was observed in young smokers. Abstract: Cigarette smoking during young adult may result in serious health issues in later life. Hence, it is extremely necessary to study the smoking neurophysiological mechanisms in this critical transitional period. However, few studies revealed the electrophysiological mechanisms of cognitive processing biases in young adult smokers. In present study, nineteen young smokers with 12 h abstinent and 19 matched nonsmokers were recruited. By employing event-related potentials (ERP) measurements during a smoking cue induced craving task, electrophysiological brain responses were compared between the young adult smokers and nonsmokers. The Slow Positive Wave (SPW) amplitude of smoking-related cues was enhanced in young adult smokers compared with nonsmokers. In addition, increased P300/SPW component of smoking-related cues relative to neutral cues were found in young adult smokers. Meanwhile, a positive correlation between Cigarette Per Day (CPD) and the amplitude of ERPs wave (P300/SPW) at anterior (Fz), central (Cz) were observed in young adult smokers. Our findings provided direct electrophysiological evidence for the cognitive processing bias of smoking cue and may shed new insights into the smoking behavior in young adult smokers.